Biofilm Formation and Antimicrobial Susceptibility of E. coli Associated With Colibacillosis Outbreaks in Broiler Chickens From Saskatchewan - Sivaranjani, Murugesan; McCarthy, Madeline C.; Sniatynski, Michelle K.; Wu, Linzhi; Dillon, Jo-Anne R.; Rubin, Joseph E.; White, Aaron P. (Frontiers in Microbiology, 2022)
The global poultry industry has grown to the extent that the number of chickens on Earth now well exceeds the number of humans. Escherichia coli infections in poultry cause significant morbidity and economic losses for producers each year. We screened 94 E. coli isolates from 12 colibacillosis outbreaks on Saskatchewan farms for antimicrobial resistance and biofilm formation. 56 isolates were from broilers with confirmed colibacillosis (systemic E. coli), and 38 isolates were from healthy broilers in the same flocks (cecal E. coli). Resistance to penicillins, tetracyclines, and aminoglycosides was common in isolates from all 12 outbreaks, while cephalosporin resistance varied by outbreak. Most E. coli were able to form biofilms in at least one of three growth media (1/2 TSB, M63, and BHI broth). In general, systemic E. coli strains were more drug-resistant and more likely to form biofilms in nutrient-rich media (BHI) than in minimal media (1/2 TSB and M63). However, on a strain-to-strain basis, we determined that there was no clear correlation between antimicrobial resistance and biofilm formation. The 21 strongest biofilm forming strains were equally comprised of drug resistant and susceptible, systemic and cecal isolates. We also tested the bactericidal efficacy of four different disinfectants against planktonic (single) cells and biofilm cells of both systemic and cecal isolates. All selected disinfectants effectively killed the planktonic cells at concentrations lower than the supplier recommended concentration, however the resistance of biofilm cells was 2- to 64-fold higher. The bactericidal efficacies of disinfectants Virocid and Virkon did not vary between the systemic and cecal biofilms, but there were notable differences between the strains treated with quaternary ammonium and hydrogen peroxide. Our results speak to the complex lifestyles and evolutionary pressures leading to diversity in E. coli poultry isolates.